2012
DOI: 10.1007/s12011-012-9551-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Status of Children with Autism vs. Neurotypical Children and the Association with Autism Severity

Abstract: This study investigates both the level of toxic metals in children with autism and the possible association of those toxic metals with autism severity. This study involved 55 children with autism ages 5-16 years compared to 44 controls with similar age and gender. The study included measurements of toxic metals in whole blood, red blood cells (RBC), and urine. The autism group had higher levels of lead in RBC (+41 %, p = 0.002) and higher urinary levels of lead (+74 %, p = 0.02), thallium (+77 %, p = 0.0001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 35 publications
7
101
4
4
Order By: Relevance
“…This outcome does not concur with a study by Elsheshtawy et al in which Hg, but not Pb, was found in the hair of autistic patients as a biochemical correlate to disease severity (CARS) [33]. However, our results are consistent with the recent work of Adams et al [34] who reported that children with autism have higher average levels of several toxic metals, among which Hg and Pb are strongly associated with variations in the severity of the disorder. However, in their study, Adams et al found a nonsignificant difference of Hg in children with autism vs. neurotypical children.…”
Section: Discussioncontrasting
confidence: 65%
“…This outcome does not concur with a study by Elsheshtawy et al in which Hg, but not Pb, was found in the hair of autistic patients as a biochemical correlate to disease severity (CARS) [33]. However, our results are consistent with the recent work of Adams et al [34] who reported that children with autism have higher average levels of several toxic metals, among which Hg and Pb are strongly associated with variations in the severity of the disorder. However, in their study, Adams et al found a nonsignificant difference of Hg in children with autism vs. neurotypical children.…”
Section: Discussioncontrasting
confidence: 65%
“…Furthermore, exposure to lead and methyl mercury has been shown to be potentially involved in autism development, while little information is available for cadmium. Many investigations indicate that autistic children have a decreased ability to excrete toxic metals and the reduced excretion combined with the relatively long half-life of these elements lead to their accumulation in tissues (Adams et al 2012). Moreover, the level of toxic metal body burden seems to be associated with the severity of autism symptoms, as shown by Adams et al (2009) who measured the body burden of toxic metals by giving dimercaptosuccinic acid, an oral chelator, and measuring the urinary excretions of metallic elements before and after the drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, measurements in whole baby teeth had shown two-to threefold higher level of mercury in autistic children with respect to the control group ). The contradictory results may derive from different deposition of mercury in the two matrices, whereas dentin is living in tissue from the origin to the lost of tooth, enamel is completely formed only by 3-12 months of age (Ash and Nelson 2003;Adams et al 2012). A positive relationship has been also reported between Hg levels both in whole blood and red blood cells, and the degree of severity of autism (DeSoto and Hitlan 2007;Geier et al 2010).…”
Section: Mercury and Asdsmentioning
confidence: 99%
“…Compared to those of controls, blood samples from the individuals with ASD showed greater amounts of lead in the red blood cells, while their urine samples showed higher tin, tungsten, and lead levels. 23 Transmethylation is also involved in the regeneration and conversion of methionine into S-adenosylmethionine, which is the most important enzymatic co-factor in the transfer of methyl groups for the biosynthesis of DNA, RNA, proteins, phospholipids, creatinine, and neurotransmitters. 22 …”
Section: Sulfur Metabolismmentioning
confidence: 99%